Inventarisasi Gas Rumah Kaca Asal Jerami Padi serta Upaya Perbaikan Kualitasnya sebagai Pakan Ternak - Ikke Yuliarti; Anis Tatik Maryani; Afzalani Afzalani; Fachroerrozi Hoesni (Universitas Batanghari Jambi, 2022)
Rice fields, especially rice straw, is one part of the agricultural sector that contributes to global warming. It is estimated that about 1% of global warming comes from rice fields. One of the efforts that can be done in reducing the contribution of paddy fields is to utilize the remaining harvest in the form of rice straw as animal feed. However, the utilization of rice straw is constrained by its low nutritional value. Therefore it is necessary to carry out ammonia to improve its quality. This study was conducted to determine the potential of rice straw to produce methane gas and to improve its quality using ammonia technology as ruminant feed. This study used a completely randomized design with four urea levels (0, 2, 4, 6% w/w) and six replications. The variables measured were gas production, methane production, total volatile fatty acids (TVFA), metabolic energy (ME), dry matter digestibility (DMD), and organic matter digestibility (OMD). The data obtained were analyzed using analysis of variance, and differences between means using Duncan's multiple range test with a confidence level of P <0.05. The results of the calculation of the production of methane (CH4) and carbon dioxide (CO2) from rice straw in Jambi Province in 2021 reached 9,024 Gg CH4 per year and Carbon 3362,167 per year. The results of ammonium hay showed that urea level had a significant effect (P<0.05) on total gas production, gas production of CH4, DMD, OMD, TVFA, and ME. The ammoniated rice straw with urea level up to 4% was the best treatment for total gas production, CH4, TVFA, and ME production. The results of the study concluded that ammoniated rice straw with 4% urea content was the best treatment to improve the quality of rice straw as ruminant feed.